HUBUNGAN STATUS GIZI DENGAN KOMPLIKASI DIABETES MELITUS TIPE 2 DI RUMAH SAKIT ISLAM SITI RAHMAH - Pera Siska; Melya Susanti; Ferry Iskandar Kahrisma (Yayasan Nusantara Hasana Berdikari, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with an increasing prevalence worldwide and is a major contributor to both microvascular and macrovascular complications. Nutritional status, particularly obesity, is considered to play a key role in the pathogenesis of these complications through mechanisms involving insulin resistance, chronic inflammation, and atherogenic dyslipidemia. However, locally based evidence on the association between nutritional status and T2DM complications remains limited. This research to evaluate the relationship between nutritional status, as measured by body mass index (BMI), and the types of T2DM complications among patients hospitalized at RSI Siti Rahmah Padang. This observational analytic study with a cross-sectional design included 65 T2DM patients with complications admitted between 2019 and 2021. Nutritional status was classified according to the WHO Western Pacific Region criteria, while complications were categorized into macroangiopathy, microangiopathy, and combined forms. Data were analyzed using the Kruskal–Wallis test with a significance level of p<0.05. Most patients were classified as having normal nutritional status (33.8%), followed by class I obesity (26.2%) and overweight (24.6%). Macroangiopathy was the most common complication (50.8%), followed by microangiopathy (46.2%) and combined complications (3.1%). Statistical analysis showed no significant association between nutritional status and the types of complications (p=0.052). BMI-based nutritional status was not significantly associated with the types of T2DM complications. Central adiposity indicators, such as waist circumference, may provide a more accurate measure of risk. Further studies with larger sample sizes are recommended.